Mineral deficiencies of cattle in Paiaguás-region in Pantanal Mato-grossense. II. Copper, zinc, manganese and iron - Brum, Paulo A. R. de; Sousa, Júlio Cesar de; Comastri Filho, José A.; Almeida, Irajá L. de (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out in order to identify levels of copper, zinc, manganese and iron in three geomorphic units, five species of pasture, and in the liver of lactating beef cows in Paiaguás region, lowlands of Mato Grosso State, Brazil. Independent of geomorphic units and pasture species, the average levels of copper ranged from 0.3 ppm to 0.7 ppm, in pasture from 2.0 ppm to 3.1 ppm and in flue liver, from 155.3 ppm to 339.9 ppm; zinc in soil, from 0.7 ppm to 1.6 ppm, in pasture from 5.6 ppm to 7.1 ppm and in the liver from 44.5 ppm to 233.8 ppm; manganese in the soil, from 17.0 ppm to 26.0 ppm, in pasture from 272.7 ppm to 477.5 ppm and in liver, from 31.5 ppm to 35.2 ppm; iron in soil, from 88.9 ppm to 174.9 ppm, in pasture from 73.0 to 472.8 ppm and in liver from 579.5 ppm to 1,015.3 ppm. Results showed that: a) soils produced pasture with low levels of copper and zinc, to lactating cow; b) manganese and iron presents in pasture attending to lactating cows needs; c) iron present in pasture in August and February reached toxic levels to cattle; d) animals showed zinc deficiency in August, February and May; e) animals showed neither manganese and iron deficient levels during experimental period nor zinc deficiency in November.